Synthesis of Some Pyrimidine, Pyrazole, and Pyridine Derivatives and Their Reactivity Descriptors - Nour E. A. Abd El-Sattar; Eman H. K. Badawy; M. S. A. Abdel-Mottaleb (Journal of Chemistry)
A series of novel pyrimidine (2, 3), pyrazole (4, 5), and pyridine (6) derivatives were synthesized using a chalcone-bearing thiophene nucleus (1). The target compounds were synthesized by reaction of compound (1) with urea, thiourea, malononitrile, hydrazine hydrate, and 2,4-dinitrophenyl hydrazine, respectively. Molecular electronic structures have been modeled within density functional theory framework (DFT). Reactivity indices and electrostatic surface potential maps (ESP maps) allow us to establish trends that enable making predictions about chemical characteristics of the newly synthesized molecules and their proton transfer tautomers. Proton transfer is generally more favored in solution than in the gas phase. In acetonitrile, keto-form tautomers and thione-form tautomers become more energetically stable than the corresponding enol or thiol tautomers due to solvent-induced enhancement in the molecular polarity identified by computed dipole moment.